Managing leaf-cutting ants: Peculiarities, trends and challenges - Lucia, Terezinha Della; Gandra, Laila C (published online, 2014)
Leaf-cutting ants are generally recognized as important pest species in Neotropical America. They are eusocial insects that exhibit social organization, foraging, fungus-cultivation, hygiene and a complex nest structure, which render their management notoriously difficult. A lack of economic thresholds and sampling plans focused on the main pest species preclude the management of leaf-cutting ants; such management would facilitate their control and lessen insecticide overuse, particularly the use of insecticidal baits. Recent restrictions on the use of synthetic compounds for such purposes impose additional challenges for the management of leaf-cutting ants. Considerable effort has been exerted regarding these challenges, which are addressed herein, but which also remain challenges that are yet to be conquered. c 2013 Society of Chemical Industry
full text
Keywords: Acromyrmex; ant baits; Atta; control; control shortcomings; management problems